The Use of New Control Card for Health Education about Chemotherapy Procedures for Patients - Tumini Tumini (Humanistic Network for Science and Technology (HNST), 2017)
In every stage of long and complex chemotherapy procedure, of course, it could confuse patients. The purpose of this queasy experimental research was to analyze the effect of education from nurses about chemotherapy procedure on patient's knowledge level toward the use of new card at one-stop oncology poly (POSA (Poli Onkologi Satu Atap)) of Dr. Soetomo Hospital, Surabaya, by using